IMPROVING STUDENTS READING COMPREHENSION THROUGH SCANNING TECHNIQUE AT THE SECOND GRADE OF THE JUNIOR HIGH SCHOOL - Djuma, Revaldo Irenius; Palengkahu, Noldy; Sanger, Maikel B.G (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
The purpose of the research paper Enhancing Students Reading Comprehension Through the Scanning Technique was to look at the usage of scanning techniques in improving students reading comprehension at SMP Berea Tondano This study included twenty eight eighth grade pupils The research approach used was classroom action research The information was acquired from a variety of sources including observations at each cycle meeting and a questionnaire The average scores in cycle two Y1 = 18 5 were higher than in cycle one Y1 = 5 95 according to the findings of this study Furthermore according to the results of the students survey 77 percent of students chose agree and 33 percent chose very agree to employ scanning approach in comprehending narative texts This research is expected to aid in the teaching of English Furthermore it is advised that future scholars look at the usage of scanning techniques in other books < p> Keywords < strong> nbsp;< em>: nbsp; nbsp; Experiments reading comprehension scanning technique< em>< p>